2013
DOI: 10.3390/biology2041242
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Bacterial Flagellum in Adhesion and Virulence

Abstract: The bacterial flagellum is a complex apparatus assembled of more than 20 different proteins. The flagellar basal body traverses the cell wall, whereas the curved hook connects the basal body to the whip-like flagellar filament that protrudes several µm from the bacterial cell. The flagellum has traditionally been regarded only as a motility organelle, but more recently it has become evident that flagella have a number of other biological functions. The major subunit, flagellin or FliC, of the flagellum plays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
372
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(382 citation statements)
references
References 100 publications
4
372
1
5
Order By: Relevance
“…Flagella organelles may act as virulence factors because motility is crucial for the action of pathogenic bacteria (5,6). About 25 different proteins are involved in the assembly of the flagellum, which is divided into five parts: the basal body, hook, hook-filament junction, filament, and filament cap.…”
mentioning
confidence: 99%
“…Flagella organelles may act as virulence factors because motility is crucial for the action of pathogenic bacteria (5,6). About 25 different proteins are involved in the assembly of the flagellum, which is divided into five parts: the basal body, hook, hook-filament junction, filament, and filament cap.…”
mentioning
confidence: 99%
“…Indeed, studies support that flagellum is important for biofilm formation in PAO1 as a non-motile strain (carrying a mutation in flgK -hook-filament junctional protein) fails to swim and to attach onto PVC surfaces [22,26]; the authors concluded to a role of PAO1 flagella in cell-to-surface interactions in the initial stages of biofilm formation. Besides, PAO1 flagellum components, such as the flagellar cap protein FliD and flagellinFliC, are important for adhesion since ∆fliCand ∆fliDmutants do not bind biotic surface such as human airway mucins [27]. Thus, the functional characterization of PAO1 flagellum may be a credible starting point to elucidate the inhibition of biofilm formation induced by F1 and therefore deserves further exploration.…”
Section: Resultsmentioning
confidence: 99%
“…These EN present flagella made of flagellin, which are proteins identified as pathogen-associated molecular patterns (PAMPs), and recognized by receptor Toll-like 5 (TLR5) (Hayashi et al, 2001;Yoon et al, 2012). TLR5 are expressed on intestinal epithelial cells and tissue macrophages, leading to the activation and secretion of pro-inflammatory cytokines, such as IL-1β (Haiko & Westerlund, 2013;Keestra et al, 2013). The observed increase in IL-1β may have also been the result of stimulation by the lipopolysaccharide (LPS) present in those EN genera.…”
Section: Influence Of Covering Reused Broiler Litter With Plastic Canmentioning
confidence: 99%